CORPORATE SOCIAL RESPONSIBILITY OF CHEMICAL FERTLIZER COMPANIES – A STUDY WITH SPECIAL REFERENCE TO FERTILIZERS AND CHEMICALS TRAVANCORE LIMITED (FACT) - MANJULA.R (Journal of Advanced Computing and Communication Technologies, 2015)
The era of corporate organizations paying lip service to social responsibility is fast coming to an end. The recent past has seen corporate social responsibility becoming a process from a concept and also organizations deriving value from this initiative. The purpose of the present paper is to study innovative practices of CSR by Indian Corporates and also the level of CSR initiatives taken by the FACT Cochin Division. Though there are several industries in the Indian corporate sector, the Chemical industry is considered as one of the highly polluting industries. Therefore the researcher has taken a special effort to analyse the social commitment of this company with financial as well as market performance. The study mainly explores the various Corporate Social Responsibilities (CSR) of FACT Ltd. The paper examines how the Company, view and conduct their CSR activities. The study is based on secondary data collection and use of content analysis technique to assess CSR practices of Chemical Industries.